The potential of improving napier grass under smallholder dairy farmers' conditions in Kenya. - Kariuki, J.N. (Wageningen University & Research, 1998)
Dairy farming is the main livestock enterprise in the mixed crop/livestock farming system in the high rainfall areas of Kenya. These areas are characterised by a high human population density and very small farms. As a consequence, napier grass ( Pennisetum purpureum ) has been widely adopted because of its relatively high dry matter yield and suitability as a cut fodder. The conventional methods of improving napier grass quality through fertilization or use of concentrates to supplement napier grass diets is limited because most farmers cannot afford these inputs. This has led to poor animal performance mostly attributed to the low protein content in napier grass.The most vulnerable group are heifers which receive far less attention compared to calves and cows. This is reflected by low weight gain (less than 0.25 kg day -1) and poor reproductive and life-time performance. Fortunately, several protein-rich forages (PRF) which have the potential to improve the quality of napier grass-based diets have been identified. These include Desmodium spp., Calliandra calothyrsus, Leucaena leucocephala, Ipomoea batatas, Medicago sativa, Musa sapienta, Trifolium semipilosum and Canna edulis .The benefits of using PRF include improved rumen function, increased energy and protein intake, improved feed efficiency, increased availability of minerals and vitamins, and generally enhanced animal performance. Appropriate and adequate information on the nutritive value of napier grass at different stages of growth and the PRF would facilitate ration formulation, allow more reliable prediction of subsequent animal performance and assist in the planning of suitable feeding strategies for the resource poor dairy farmers. Therefore, the overall objective of the study was to evaluate the nutritive value of napier grass and determine the potential for improvement in animal performance using PRF. Results from this thesis indicated that intake and utilization can be improved by manipulating the cutting regime of napier grass and varying the levels of PRF supplements.Indeed, PRF had a profound effect on fermentation and subsequently improved the intake of organic matter fermented in the rumen by up to 50%. Protein supplementation strategies for low crude protein tropical grasses should first target at optimising microbial protein production and then consider supplements containing a combination of ruminally degradable and bypass protein for high animal performance. Inadequately fed heifers grow poorly and show poor reproductive performance. The positive growth response obtained from the supplemented heifers were attributed to additional rumen degradable protein and/or bypass protein from PRF that overcame protein deficiency in napier grass.It was concluded that PRF could play an important role in the improvement of the utilization of napier grass and the subsequent animal performance. The data provided in this study, on the nutritive value of these forages will, consequently, facilitate making appropriate choices for diet formulation at the farm level.